The Strategy For Learning Main Clause And Subordinate Clause: English - Nazwa Nadia; Fauziah Amna Sipahutar; Romadhan Siregar; Pausi Rahman; Yani Lubis (JELT : Journal of English Education, Teaching and Literature, 2024)
This article discusses the challenges faced by English language learners in understanding main and subordinate clauses. The research involved analyzing respondents who demonstrated difficulties in comprehending basic concepts, identifying conjunctions, and punctuating correctly. Findings revealed that 70% of respondents struggled to recognize conjunctions that mark subordinate clauses, and 60% of respondents experienced difficulties in punctuation. This research supports the importance of explicit instruction in learning clause structures, as well as the need for more visual and practice-based teaching strategies. Using diagrams, concept maps, and context-based exercises is expected to enhance students' understanding of clauses. The article suggests a shift from a theoretical approach to direct practice to help students overcome difficulties in learning clauses.